2020
DOI: 10.3892/ol.2020.11741
|View full text |Cite
|
Sign up to set email alerts
|

MKP‑1 overexpression is associated with chemoresistance in bladder cancer via the MAPK pathway

Abstract: Mitogen activated protein kinase phosphatase-1 (MKP-1) has been revealed to be overexpressed in bladder cancer, particularly in non-muscle invasive bladder cancer. MKP-1 may also be associated with chemotherapy resistance. However, the underlying mechanism is yet to be elucidated. The current study investigated the expression of MKP-1 by performing immunohistochemistry in surgically resected specimens obtained from primary and recurrent patients with bladder cancer. The results revealed that MKP-1 expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Therefore, overexpression of TNFAIP8L3, caused by hypomethylation, may contribute to BLCA progression or resistance to therapies. MAPK signaling and JAK-STAT signaling pathways have been shown to have vital roles in BLCA progression and might be connected with TNFAIP8L3 activation ( Huang et al, 2020 ; Lei et al, 2020 ), but the mechanisms connecting TNFAIP8L3 and these two pathways remain unclear. Further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, overexpression of TNFAIP8L3, caused by hypomethylation, may contribute to BLCA progression or resistance to therapies. MAPK signaling and JAK-STAT signaling pathways have been shown to have vital roles in BLCA progression and might be connected with TNFAIP8L3 activation ( Huang et al, 2020 ; Lei et al, 2020 ), but the mechanisms connecting TNFAIP8L3 and these two pathways remain unclear. Further studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MMP7 can be used as a related effector of invasion and metastasis. Similarly, MKP-1 is overexpressed in several cancer types, associated with cancer progression, and may be a potential prognostic marker 35 . In T-ALL cell lines, cells with MKP-1 deficiency exhibited compromised tumorigenicity, which was regulated by Notch3 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The results from KEGG analysis indicated that MAPK, PI3K-Akt, and HIF-1 signaling pathways were markedly identified. MAPK and PI3K-Akt regulate tumor cell survival, proliferation, growth, mobility, and angiogenesis, whose activations were essential for BLCA metastasis and chemotherapy ( Xia et al, 2018 ; Sun et al, 2019 ; Lei et al, 2020 ; Ruan et al, 2020 ; Zhang et al, 2020 ; Xu et al, 2021a ; Kao et al, 2021 ). The HIF-1 signaling pathway was also discovered to be involved in hypoxic BLCA cell proliferation, migration, invasion, metastasis, and EMT, providing a rationale for clinical trials evaluating agents targeting this pathway ( Tickoo et al, 2011 ; Xue et al, 2014 ; Lu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%